Synthetic method for preparing high-entropy doped vanadium-based oxide microcrystal positive electrode material through mixed alcohol precipitation
Through a mixed alcohol analysis method with low energy consumption at room temperature, a high entropy doped vanadium-based oxide microcrystalline positive electrode material was prepared, which solved the difficulty in controlling the temperature pressure and difficult to remove by-products during the preparation of vanadium-based oxide materials in the prior art. The problem has achieved a significant improvement in the high doping and electrochemical properties of the material.
Patent Information
- Application Number
- CN202411677038.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
AI Technical Summary
The existing methods for preparing vanadium-based oxide positive electrode materials have problems such as difficult to control the temperature pressure, difficult to remove by-products, and inability to achieve the expected results.
Using a mixed alcohol analysis method with low energy consumption at room temperature, rapid crystallization was performed by a mixed solution of ethanol and glycerol to prepare a high-entropy doped vanadium-based oxide microcrystalline positive electrode material. The method includes weighing the mixture of the vanadium source and the metal salt solution, performing alcohol analysis treatment, followed by vacuum drying and heat treatment, and finally ultrasonic washing and vacuum drying to obtain a high entropy doped vanadium-based oxide microcrystalline material.
The prepared brick-shaped layered vanadium-based oxide microcrystalline material has high doping, uniform doping and controllable secondary particles, significantly improved electrochemical performance, and improved cycle life and stability.
Smart Images

Figure CN119430320A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation and application fields of positive electrode materials for aqueous zinc ion secondary batteries, and in particular to a synthesis method for preparing high-entropy doped vanadium-based oxide microcrystalline positive electrode materials by mixed alcohol precipitation. Background Art
[0002] Energy is the cornerstone of social development and is crucial to the rational use of resources, the development of a low-carbon economy and the promotion of sustainable development. The widely used lithium-ion batteries currently have safety risks and are expensive, and there is an urgent need to find new batteries to replace them. Aqueous zinc-ion batteries have attracted widespread attention due to their safety, environmental protection and low price. At present, there are three main positive electrode materials based on aqueous zinc-ion batteries: Prussian blue analogs, polymorphs of manganese dioxide and vanadium-based materials. Vanadium-based materials have greatly improved the battery cycle due to their advantages of increasing the interlayer spacing of the material and supporting the material structure.
[0003] After investigation and research, it was found that the most common method for preparing vanadium-based oxide positive electrode materials is hydrothermal method (CN117105288A); this method is conducive to accurately adjusting the reaction and controlling the structure and morphology of the material, but the temperature and pressure during the reaction are difficult to control, resulting in excessive products, and the by-products are difficult to remove, and the battery's cycle capacity and stability cannot achieve the expected effect. In addition, there are aerosol jet printing method (CN118458823A), solid melting method (CN114744197A), self-growth method (CN111952580A), electrodeposition method (CN114744197A) and other methods for preparing vanadium-based oxide positive electrode materials. The key to the aerosol jet printing method is to print out the material precursor through aerosol jet printing technology, but this method has high technical requirements and is difficult to operate; the solid melting method and self-growth method are simple and easy to operate, but they are prone to uneven doping and difficult to control particle size distribution; the use of electrodeposition method is conducive to coating the target substance, but its reaction conditions are harsh and the product is difficult to control during the process. At the same time, in the existing reported inventions, the morphology of vanadium-based oxides includes layered stacked hexagonal prisms (CN117105288A), nano-columns (CN118062892A), nano-flowers (CN118458823A), flakes (CN118791042A), nano-belts (CN114084906A), nano-needles (CN114420918A), spheres (CN103531764A), etc. In summary, there is no patent or literature reporting a brick-shaped layered vanadium-based oxide microcrystalline material with strong specificity, high doping degree, uniform doping, and controllable secondary particles obtained by simple and low-energy solid-liquid separation at room temperature. In view of the shortcomings of the prior art, the present invention reports for the first time a method for simply and efficiently synthesizing a high-entropy doped vanadium-based oxide aqueous battery microcrystalline positive electrode material by treating a vanadium source and a plurality of doping element metal salts with mixed alcohol precipitation. Summary of the invention
[0004] The purpose of the present invention is to provide a method for synthesizing a high-entropy doped vanadium-based oxide microcrystalline positive electrode material by mixing alcohol precipitation at room temperature with low energy consumption in order to solve the deficiencies in the prior art. The brick-shaped layered vanadium-based oxide microcrystalline material prepared by the present invention has a pure product, a high doping degree and uniform doping, and its electrochemical performance is significantly improved.
[0005] The synthesis of a high entropy doped vanadium-based oxide microcrystalline positive electrode material prepared by mixed alcohol precipitation
[0006] The method is characterized in that the molecular formula of the microcrystalline positive electrode material is as follows:
[0007] Er a Cu b Ca c Zn dMn e Co f Al g Ni h V2O5
[0008] Among them, 0.005≤a+b+c+d+e+f+g+h≤0.015;
[0009] Among them, the doping element Er is trivalent, Cu is divalent, Ca is divalent, Zn is divalent, Mn is divalent, Co is divalent, Al is trivalent, and Ni is divalent.
[0010] The method for synthesizing a high entropy doped vanadium-based oxide microcrystalline positive electrode material by mixed alcohol precipitation is characterized by comprising the following steps:
[0011] Step 1: Weigh 0.0025 mol of vanadium source and heat and stir in 30 mL of deionized water until completely dissolved, control the temperature at 70-75° C., prepare 0.025 mol / L of each metal salt solution, then add 0.1-0.5 mL of each metal salt solution prepared according to the determined high entropy doped vanadium-based oxide molecular formula, stir evenly for 0.5-2 min, and obtain a mixed solution.
[0012] Step 2: The mixed solution in step 1 is rapidly crystallized by mixed alcohol precipitation, and the high entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material precursor is collected by centrifugation or vacuum filtration.
[0013] Step 3: vacuum-dry the high-entropy doped vanadium-based oxide precursor in step 3 to obtain a high-entropy doped vanadium-based oxide pre-product, control the temperature to 60-80° C., and control the time to 10-12 hours.
[0014] Step 4: The high entropy doped vanadium-based oxide pre-product in step 3 is heated to 380-500° C. at a heating rate of 2-5° C. / min in an air atmosphere, kept at that temperature for 3-4 hours, and then naturally cooled to room temperature to obtain a sintered product.
[0015] Step 5: The sintered product in step 4 is first ultrasonically washed, then collected by centrifugation or vacuum filtration, and vacuum dried to obtain a high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material.
[0016] The method for synthesizing a high-entropy doped vanadium-based oxide microcrystalline positive electrode material by mixed alcohol precipitation is characterized in that in step 2, during the rapid crystallization process, the solution used is a mixed solution of ethanol and glycerol, the total volume of the mixed solution is 100 mL, and the volume ratio of ethanol to glycerol is 7:3.
[0017] The method for synthesizing a high-entropy doped vanadium-based oxide microcrystalline positive electrode material by mixed alcohol precipitation is characterized in that: in step 5, in the ultrasonic washing process, the mass ratio of deionized water to the sintered product after heat treatment is 10:1, and the number of ultrasonic washings is 2 to 3 times; in the vacuum drying process, the temperature is controlled at 60 to 80°C and the control time is controlled at 10 to 12 hours.
[0018] The method for synthesizing a high entropy doped vanadium-based oxide microcrystalline positive electrode material by mixed alcohol precipitation is characterized in that: in step 1:
[0019] The vanadium source is ammonium metavanadate;
[0020] The metal salts are:
[0021] Erbium salts are erbium nitrate hexahydrate, erbium chloride, and erbium sulfate;
[0022] The copper salt is copper chloride or copper sulfate pentahydrate;
[0023] The calcium salt is calcium chloride;
[0024] The zinc salt is zinc sulfate, zinc nitrate or zinc chloride;
[0025] The manganese salt is manganese sulfate or manganese chloride;
[0026] The cobalt salt is cobalt sulfate or cobalt nitrate;
[0027] The aluminum salt is aluminum nitrate or aluminum sulfate;
[0028] The nickel salt is nickel sulfate, nickel nitrate or nickel chloride.
[0029] Technical Effects
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The doping of various metal ions not only increases the interlayer spacing of vanadium-based materials, but also provides more ion channels, making Zn 2+ During the charge and discharge process, the energy loss caused by the restricted movement of ions is reduced, and the overall efficiency and cycle life of the battery are improved; at the same time, a variety of metal ions play a "pillar" role between the layers, which further improves the stability of the material structure. In addition, with the increase of system uncertainty, the formation of electronic conduction paths is promoted, thereby improving the conductivity of the material. The use of mixed alcohol precipitation greatly reduces the loss of ethanol and increases the amount of precipitation in the rapid crystallization process; after the experiment is completed, the solution after alcohol precipitation can be recycled and reused. The preparation method is simple, efficient, and environmentally friendly, which improves the utilization rate of atoms, conforms to the principles of green chemistry, and provides a new idea for the preparation of positive electrode materials for vanadium-based oxide batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the XRD diagram of some samples of the vanadium-based microcrystalline positive electrode material powder obtained in Example 1 of the present invention.
[0033] Figure 2 This is a SEM image of a portion of the sample of the vanadium-based microcrystalline positive electrode material powder obtained in Example 1 of the present invention.
[0034] Figure 3 This is a total element distribution map of a portion of the sample of the vanadium-based microcrystalline positive electrode material powder obtained in Example 1 of the present invention.
[0035] Figure 4 The graphs are the cycle performance and coulomb efficiency curves of aqueous zinc ion button batteries prepared from the vanadium-based microcrystalline positive electrode material powder sample obtained in Example 1 of the present invention.
[0036] Figure 5 The figure is a charge and discharge curve diagram of an aqueous zinc ion button battery prepared from the vanadium-based microcrystalline positive electrode material powder sample obtained in Example 1 of the invention.
[0037] Figure 6 The CV curve of an aqueous zinc ion button battery prepared from the vanadium-based microcrystalline positive electrode material powder sample obtained in Example 1 of the invention.
[0038] Figure 7 This is a SEM image of a portion of the sample of the vanadium-based microcrystalline positive electrode material powder obtained in Example 2 of the present invention.
[0039] Figure 8 The graphs are the cycle performance and coulomb efficiency curves of aqueous zinc ion button batteries prepared from the vanadium-based microcrystalline positive electrode material powder sample obtained in Example 2 of the present invention.
[0040] Fig. 9 The figure is a charge and discharge curve diagram of an aqueous zinc ion button battery prepared from the vanadium-based microcrystalline positive electrode material powder sample obtained in Example 2 of the invention.
[0041] Fig.10 This is a CV curve diagram of an aqueous zinc ion button battery prepared from the vanadium-based microcrystalline positive electrode material powder sample obtained in Example 2 of the invention.
[0042] Fig.11 This is a SEM image of a portion of samples of vanadium-based microcrystalline positive electrode material powder obtained in implementation three of the present invention.
[0043] Fig.12 This is a SEM image of a portion of the sample of the vanadium-based microcrystalline positive electrode material powder obtained in Example 4 of the present invention. DETAILED DESCRIPTION
[0044] The following examples are used to illustrate the present invention, but the embodiments of the present invention are not limited thereto, and are specifically carried out according to the following implementation methods:
[0045] Embodiment 1:
[0046] The present invention discloses a method for synthesizing a high entropy doped vanadium-based oxide aqueous battery microcrystalline positive electrode material by mixed alcohol precipitation. The specific operation scheme is: weigh 0.0025 mol of vanadium source, and prepare erbium sulfate, copper chloride, calcium chloride, zinc sulfate, manganese sulfate, cobalt sulfate, aluminum nitrate, and nickel sulfate solutions with a concentration of 0.025 mmol / mL, heat and stir the weighed vanadium source in water until it is completely dissolved, and then according to the determined molecular formula Er 0.0015 Cu 0.0015 Ca 0.0015 Zn 0.001 Mn 0.0005 Co 0.0005 Al 0.0005 Ni 0.0005 V2O5 was added with 0.3 ml of erbium sulfate solution, 0.3 ml of copper chloride solution, 0.3 ml of calcium chloride solution, 0.1 ml of zinc sulfate solution, 0.1 ml of manganese sulfate solution, 0.1 ml of cobalt sulfate solution, 0.1 ml of aluminum nitrate solution and 0.1 ml of nickel sulfate solution, and stirred for 1 min to obtain a mixed solution, which was then rapidly crystallized in a mixed solution of 100 ml of ethanol and glycerol, and then centrifuged to obtain a precursor of a positive electrode microcrystalline material of a high-entropy doped vanadium-based oxide aqueous battery. The precursor of the microcrystalline material is dried in a vacuum drying oven at 60°C for 12 hours to obtain a pre-product of high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material. The pre-product of high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material is heated to 580°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 4 hours, and then naturally cooled to room temperature for heat treatment to obtain a sintered product. The sintered product is first ultrasonically washed, then collected by reduced pressure filtration, and dried in a vacuum drying oven at 80°C for 10 hours to obtain high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material powder. The powder, conductive agent acetylene black and binder polyvinylidene fluoride (PVDF) were ground in N-methylpyrrolidone (NMP) solvent in a mass ratio of 7:2:1 until they were evenly mixed, and then coated on stainless steel foil. After drying in a vacuum drying oven at 60°C for 12 hours, they were cut into discs with a diameter of 12 mm as the positive electrode; then a round zinc sheet with a diameter of 16 mm was used as the negative electrode, 2 mol / L ZnSO4 was used as the electrolyte, and glass fiber was used as the diaphragm. The battery was assembled in a 2032-type battery shell and sealed to obtain an aqueous zinc ion battery. The constant current charge and discharge test voltage range is 0.2-1.6V, the current density is 1A / g; the CV test voltage range is 0.2-1.6V, and the scan rate is 0.1mV / s.
[0047] Embodiment 2:
[0048] The present invention discloses a method for preparing a high entropy doped vanadium-based oxide aqueous battery microcrystalline positive electrode material by mixed alcohol precipitation. The specific operation scheme is: weigh 0.0025 mol of vanadium source, and prepare erbium sulfate, copper chloride, calcium chloride, zinc sulfate, manganese sulfate, cobalt sulfate, aluminum nitrate, and nickel sulfate solutions with a concentration of 0.025 mmol / mL, heat and stir the weighed vanadium source in water until it is completely dissolved, and then according to the determined molecular formula Er 0.001 Cu 0.001 Ca 0.001 Zn 0.001 Mn 0.001 Co 0.001 Al 0.001 Ni 0.001 V2O5 was added with 0.2 mL of erbium sulfate solution, 0.2 mL of copper chloride solution, 0.2 mL of calcium chloride solution, 0.2 mL of zinc sulfate solution, 0.2 mL of manganese sulfate solution, 0.2 mL of cobalt sulfate solution, 0.2 mL of aluminum nitrate solution, and 0.2 mL of nickel sulfate solution, and stirred for 1 min to obtain a mixed solution, which was then rapidly crystallized in a mixed solution of 100 mL of ethanol and glycerol, and then centrifuged to obtain a precursor of a positive electrode microcrystalline material of a high-entropy doped vanadium-based oxide aqueous battery. The precursor of the microcrystalline material is dried in a vacuum drying oven at 60°C for 12 hours to obtain a pre-product of high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material. The pre-product of high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material is heated to 580°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 4 hours, and then naturally cooled to room temperature for heat treatment to obtain a sintered product. The sintered product is first ultrasonically washed, then collected by reduced pressure filtration, and dried in a vacuum drying oven at 80°C for 10 hours to obtain high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material powder. The powder, conductive agent acetylene black and binder polyvinylidene fluoride (PVDF) were ground in N-methylpyrrolidone (NMP) solvent in a mass ratio of 7:2:1 until they were evenly mixed, and then coated on stainless steel foil. After drying in a vacuum drying oven at 60°C for 12 hours, they were cut into discs with a diameter of 12 mm as the positive electrode; then a round zinc sheet with a diameter of 16 mm was used as the negative electrode, 2 mol / L ZnSO4 was used as the electrolyte, and glass fiber was used as the diaphragm. The battery was assembled in a 2032-type battery shell and sealed to obtain an aqueous zinc ion battery. The constant current charge and discharge test voltage range is 0.2-1.6V, the current density is 1A / g; the CV test voltage range is 0.2-1.6V, and the scan rate is 0.1mV / s.
[0049] Embodiment three:
[0050] The present invention discloses a method for preparing a high entropy doped vanadium-based oxide aqueous battery microcrystalline positive electrode material by mixed alcohol precipitation. The specific operation scheme is: weigh 0.0025 mol of vanadium source, and prepare erbium sulfate, copper chloride, calcium chloride, zinc sulfate, manganese sulfate, cobalt sulfate, aluminum nitrate, and nickel sulfate solutions with a concentration of 0.025 mmol / mL, heat and stir the weighed vanadium source in water until it is completely dissolved, and then according to the determined molecular formula Er 0.0025 Cu 0.0025 Ca 0.0025 Zn 0.0015 Mn 0.0005 Co 0.0005 Al 0.0005 Ni 0.000 5V2O5 was added with 0.5 mL of erbium sulfate solution, 0.5 mL of copper chloride solution, 0.5 mL of calcium chloride solution, 0.3 mL of zinc sulfate solution, 0.1 mL of manganese sulfate solution, 0.1 mL of cobalt sulfate solution, 0.1 mL of aluminum nitrate solution, and 0.1 mL of nickel sulfate solution, and stirred for 1 min to obtain a mixed solution, which was then rapidly crystallized in a mixed solution of 100 mL of ethanol and glycerol, and then centrifuged to obtain a high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material precursor. The precursor of the microcrystalline material is dried in a vacuum drying oven at 60°C for 12 hours to obtain a pre-product of high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material. The pre-product of high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material is heated to 550°C at a heating rate of 5°C / min under an air atmosphere, kept warm for 4 hours, and then naturally cooled to room temperature for heat treatment to obtain a sintered product. The sintered product is first ultrasonically washed, then collected by reduced pressure filtration, and dried in a vacuum drying oven at 80°C for 10 hours to obtain high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material powder.
[0051] Embodiment 4:
[0052] The present invention discloses a method for preparing a high entropy doped vanadium-based oxide aqueous battery microcrystalline positive electrode material by mixed alcohol precipitation. The specific operation scheme is: weigh 0.0025 mol of vanadium source, and prepare erbium sulfate, copper chloride, calcium chloride, zinc sulfate, manganese sulfate, cobalt sulfate, aluminum nitrate, and nickel sulfate solutions with a concentration of 0.025 mmol / mL, heat and stir the weighed vanadium source in water until it is completely dissolved, and then according to the determined molecular formula Er 0.003 Cu 0.003 Ca 0.003 Zn 0.0015 Mn 0.001 Co 0.001 Al 0.001 Ni 0.001V2O5 was added with 0.6 mL of erbium sulfate solution, 0.6 mL of copper chloride solution, 0.6 mL of calcium chloride solution, 0.3 mL of zinc sulfate solution, 0.2 mL of manganese sulfate solution, 0.2 mL of cobalt sulfate solution, 0.2 mL of aluminum nitrate solution, and 0.2 mL of nickel sulfate solution, and stirred for 1 min to obtain a mixed solution, which was then rapidly crystallized in a mixed solution of 100 mL of ethanol and glycerol, and then vacuum filtered to obtain a precursor of a positive electrode microcrystalline material of a high-entropy doped vanadium-based oxide aqueous battery. The ultra-microcrystalline material precursor was dried in a vacuum drying oven at 60°C for 12 hours to obtain a pre-product of high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material. The pre-product of high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material was heated to 550°C at a heating rate of 5°C / min under an air atmosphere, kept warm for 4 hours, and then naturally cooled to room temperature for heat treatment to obtain a sintered product. The sintered product was first ultrasonically washed, then collected by reduced pressure filtration, and dried in a vacuum drying oven at 80°C for 10 hours to obtain high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material powder.
Claims
1. A method for preparing a high entropy doped vanadium-based oxide microcrystalline positive electrode material by mixed alcohol precipitation, characterized in that: The molecular formula of the microcrystalline positive electrode material is as follows: Er a Cu b Ca c Zn d Mn e What f Al g No h V2O5 Among them, 0.005≤a+b+c+d+e+f+g+h≤0.015; Among them, the doping element Er is trivalent, Cu is divalent, Ca is divalent, Zn is divalent, Mn is divalent, Co is divalent, Al is trivalent, and Ni is divalent.
2. A method for synthesizing a high entropy doped vanadium-based oxide microcrystalline positive electrode material by mixed alcohol precipitation, characterized in that: The steps include: Step 1: Weigh 0.0025 mol of vanadium source and heat and stir in 30 mL of deionized water until completely dissolved, control the temperature at 70-75° C., prepare 0.025 mol / L of each metal salt solution, then add 0.1-0.5 mL of each metal salt solution prepared according to the determined high entropy doped vanadium-based oxide molecular formula, stir evenly for 0.5-2 min, and obtain a mixed solution. Step 2: The mixed solution in step 1 is rapidly crystallized by mixed alcohol precipitation, and the high entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material precursor is collected by centrifugation or vacuum filtration. Step 3: vacuum-dry the high-entropy doped vanadium-based oxide precursor in step 3 to obtain a high-entropy doped vanadium-based oxide pre-product, control the temperature to 60-80° C., and control the time to 10-12 hours. Step 4: The high entropy doped vanadium-based oxide pre-product in step 3 is heated to 380-500° C. at a heating rate of 2-5° C. / min in an air atmosphere, kept at that temperature for 3-4 hours, and then naturally cooled to room temperature to obtain a sintered product. Step 5: The sintered product in step 4 is first ultrasonically washed, then centrifuged or vacuum filtered to collect, and vacuum dried to obtain a high-entropy doped vanadium-based oxide aqueous battery positive electrode microcrystalline material.
3. According to claim 2, a method for preparing a high entropy doped vanadium-based oxide microcrystalline positive electrode material by mixed alcohol precipitation, characterized in that: In step 2, during the rapid crystallization process, the solution used is a mixed solution of ethanol and glycerol, the total volume of the mixed solution is 100 mL, and the volume ratio of ethanol to glycerol is 7:
3.
4. According to claim 2, a method for synthesizing a high entropy doped vanadium-based oxide microcrystalline positive electrode material by mixed alcohol precipitation, characterized in that: In step 5, during the ultrasonic washing process, the mass ratio of deionized water to the sintered product after heat treatment is 10:1, and the number of ultrasonic washing is 2 to 3 times; during the vacuum drying process, the temperature is controlled at 60 to 80° C. and the control time is 10 to 12 hours.
5. According to claim 2, a method for preparing a high entropy doped vanadium-based oxide microcrystalline positive electrode material by mixed alcohol precipitation, characterized in that: In step 1: The vanadium source is ammonium metavanadate; The metal salts are: Erbium salts are erbium nitrate hexahydrate, erbium chloride, and erbium sulfate; The copper salt is copper chloride or copper sulfate pentahydrate; The calcium salt is calcium chloride; The zinc salt is zinc sulfate, zinc nitrate or zinc chloride; The manganese salt is manganese sulfate or manganese chloride; The cobalt salt is cobalt sulfate or cobalt nitrate; The aluminum salt is aluminum nitrate or aluminum sulfate; The nickel salt is nickel sulfate, nickel nitrate or nickel chloride.
Citation Information
Patent Citations
Sodium-ion battery positive material spherical ammonium vanadium oxide and preparation method therefor
CN103531764A
Preparation method of vanadium-based nano material for positive electrode of aqueous zinc ion battery
CN111952580A
Rapid preparation method of alkali metal ion intercalation vanadium oxide nanobelt and application thereof
CN114084906A
Preparation method of nano needle-shaped vanadium oxide zinc ion battery positive electrode material with oxygen vacancy
CN114420918A
Vanadium oxide-polypyrrole composite material as well as preparation method and application thereof
CN114744197A